Integrating HIV/AIDS in Vietnam's Social Health Insurance Scheme: Experience and Lessons from the Health Finance and Governance Project, 2014-2017 - Nazzareno Todini; Theodore M. Hammett; Robert Fryatt (Taylor & Francis Group, 2018)
Abstract-This article describes the lessons learned by USAID's Health Finance and Governance project over three years of implementation of health system strengthening activities in Vietnam. The authors recount the project's approach to supporting significant advancements in the government of Vietnam's (GVN) efforts to transition the financing of HIV/AIDS from donors to domestic resources, while assuring adequate coverage and financial protection for people living with HIV. Through an adaptive method of technical assistance design and delivery, the project aligned early on with the GVN's policy to finance HIV through Social Health Insurance and supported the Ministry of Health, the Vietnam Authority for AIDS Control, and the Vietnam Social Security agency in ensuring the long-term sustainability of HIV programs in the country. Major lessons included the importance of working within complex adaptive systems, the need to work within the country's existing policy framework, and the aim of creating and disseminating evidence in a cyclical fashion to sustain deliberate, persistent advocacy activities to guide and support the relevant decision makers.